The Management of Chronic Viral Hepatitis: A Canadian Consensus Conference 2004 - Morris Sherman; Vincent Bain; Jean-Pierre Villeneuve; Robert P Myers; Curtis Cooper; Steven Martin; Catherine Lowe (Canadian Journal of Gastroenterology)
Several government and nongovernment organizations held a consensus conference on the management of acute and chronic viral hepatitis to update previous management recommendations. The conference became necessary because of the introduction of new forms of therapy for both hepatitis B and hepatitis C. The conference issued recommendations on the investigation and management of chronic hepatitis B, including the use of lamivudine, adefovir and interferon. The treatment of hepatitis B in several special situations was also discussed. There were also recommendations on the investigation and treatment of chronic hepatitis C and hepatitis C-HIV coinfection. In addition, the document makes some recommendations about the provision of services by provincial governments to facilitate the delivery of care to patients with hepatitis virus infection. The present document is meant to be used by practitioners and other health care providers, including public health staff and others not directly involved in patient care.